Management of Perianal Fistulas in Crohn's Disease - Seyfried, Steffen (Visc Med, 2019)
BACKGROUND: Perianal fistulizing Crohn's disease is associated with severe symptoms such as pain, fecal incontinence, and a significant reduction in quality of life. RESULTS: In refractory cases, many patients face the decision of having a stoma and/or requiring proctectomy. In former years, the standard of care was a complete fistulectomy, bringing with it a high rate of continence disorders. Additionally, many patients received indefinite treatment, namely the placement of a seton to maintain surgical drainage. CONCLUSION: More recently, newer biologics, cell-based therapies as well as novel surgical techniques have been introduced, raising new hopes that outcomes can be improved upon.